2015
DOI: 10.1039/c5py00388a
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization and degradation of aliphatic polyesters synthesized by atom transfer radical polyaddition

Abstract: Two AB*-type inimers (4-vinylbenzyl 2-bromo-2-isobutyrate (VBBiB) and 4-vinylbenzyl 2-bromo-2-phenylacetate (VBBPA)) were synthesized and used to obtain aliphatic polyesters through atom transfer radical polyaddition (ATRPA). First, we optimized the ATRPA of VBBiB at a moderate temperature (<25°C) using a commercially available CuBr 2 /Cu(0)/dNBpy system; however, the reaction run at 70°C exhibited self-degrading behavior, as revealed by molecular weight (MW) variations in GPC traces and evidence of a five-mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Among these highly branched polymers, hyperbranched polymers receive particular interest from both industries and academia because of their one‐pot inexpensive synthesis and retention of arborescent structures. Hyperbranched polymers typically could be produced in one pot via step‐growth polymerization of multifunctional AB m (m ≥ 2) monomers, [ 7–13 ] step‐growth copolymerization of A n and B m monomers (e.g., A 2 + B 3 ), [ 14–16 ] chain‐growth polymerization of AB m (m ≥ 2) monomers, [ 17–19 ] chain‐growth copolymerization of divinyl cross‐linkers, [ 20–26 ] self‐condensing vinyl polymerization (SCVP) of polymerizable initiators (inimers), [ 27–35 ] or polymerizable transfer agents (transmers). [ 36–40 ] It is important to note that any of these methods could produce hyperbranched polymers and randomly branched polymer as their difference lies in the fraction of branching unit incorporated into the polymer backbone.…”
Section: Introductionmentioning
confidence: 99%
“…Among these highly branched polymers, hyperbranched polymers receive particular interest from both industries and academia because of their one‐pot inexpensive synthesis and retention of arborescent structures. Hyperbranched polymers typically could be produced in one pot via step‐growth polymerization of multifunctional AB m (m ≥ 2) monomers, [ 7–13 ] step‐growth copolymerization of A n and B m monomers (e.g., A 2 + B 3 ), [ 14–16 ] chain‐growth polymerization of AB m (m ≥ 2) monomers, [ 17–19 ] chain‐growth copolymerization of divinyl cross‐linkers, [ 20–26 ] self‐condensing vinyl polymerization (SCVP) of polymerizable initiators (inimers), [ 27–35 ] or polymerizable transfer agents (transmers). [ 36–40 ] It is important to note that any of these methods could produce hyperbranched polymers and randomly branched polymer as their difference lies in the fraction of branching unit incorporated into the polymer backbone.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to degrade these branched polymers under acidic condition represents an interesting property and has been achieved in hyperbranched polymers by incorporating various functional groups into the polymer architecture . Using an acetal‐containing inimer ABIEM, previously developed in our group, a copolymer was synthesized at ratios of [IEM] 0 :[ABIEM] 0 :[CuBr 2 ] 0 = 50:10:0.5.…”
Section: Resultsmentioning
confidence: 99%
“…Among the various synthetic methods, radical‐based self‐condensing vinyl polymerization (SCVP) of inimers (containing ini tiator fragment and mono mer vinyl group in one molecule) and/or transmers (containing chain trans fer group and mono mer vinyl group in one molecule) has become particularly popularly in the past two decades. All established reversible deactivation radical polymerizations (RDRP) techniques, including atom transfer radical polymerization (ATRP), nitroxide‐mediated polymerization (NMP) and reversible addition–fragmentation chain transfer (RAFT) polymerization have been intensively applied in the (co)polymerization of inimers and transmers, primarily in solution, for synthesis of branched polymers with various compositions. For instance, those synthesized by ATRP possess high density of chain‐end initiating groups and are easy to extend with vinyl monomers using the same technique .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we demonstrated a highly efficient ATRPA of AB type inimer containing an ethyl 2-bromo-2-phenylacetate (EBPA) based initiating site and a styrene group [56]. Accordingly, our previously reported 4-vinylbenzyl 2-bromo-2-phenylacetate (VBBPA) inimer possesses very high activation rate of the EBPA initiating site at the polyester chain end and high selectivity for the initiations between the chain end and the polyester backbone (i.e., benzyl halide initiating sites).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the mechanism study, the copper catalysts possess high selectivity between the initiating site at chain end (EBPA) and the initiating site at backbone (PEBr) ( k act,EBPA / k act,PEBr = ca. 30,000) [56]. Therefore, we attained fast ATRPA and obtain linear type polyesters.…”
Section: Introductionmentioning
confidence: 99%